2017
DOI: 10.1080/09581596.2017.1297384
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the person: the construction and transformation of blood as a resource

Abstract: ABSTRACT:Many studies of blood donation have looked at the motives of donors, their relationship with the wider society, and corresponding values such as gift-giving, altruism and responsibility.These underpin a rhetorical representation of person-to-person donation that neglects the many technical processes that take place between donation and eventual use and the material nature of blood itself. This ethnographic study, conducted in four UK blood donation sites, describes the various practices involved in ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Technology has impacts on the understanding and value of the blood products. R. Lynch and S. Cohn studied in the UK blood service centers how blood acquired value through all the transformations [47]. For plasma, our study showed that the technology transforming body fluid into the final product was also important because it helped to illuminate the difference between blood and plasma.…”
Section: The Localization Of the Transferred Technologymentioning
confidence: 90%
“…Technology has impacts on the understanding and value of the blood products. R. Lynch and S. Cohn studied in the UK blood service centers how blood acquired value through all the transformations [47]. For plasma, our study showed that the technology transforming body fluid into the final product was also important because it helped to illuminate the difference between blood and plasma.…”
Section: The Localization Of the Transferred Technologymentioning
confidence: 90%
“…They argue that this narrative does not accurately represent the processing of blood that takes place between collection and eventual use or address new meanings that may emerge as a result of the processing of blood. They discuss the social implications [13][14][15][16][17][18][19].…”
Section: Donated Blood As a Gift And A Commoditymentioning
confidence: 99%
“…In a case study from Belgium, Wittock and colleagues show that BCA practices of considering blood as a gift in interactions with donors and a commodity when manufactured and sold to hospitals may optimize workflows but also lead to sub-optimal communication about blood processing between donors and BCAs [13]. Moreover, the narrative of blood as a gift may not coincide with how donors understand their donations [14]. Lynch and Cohn's observations of staff and donors in donor centres in the United Kingdom provide evidence that BCAs could broaden the narratives employed in communications with donors to include explanations of how blood is processed or used for research.…”
Section: Donated Blood As a Gift And A Commoditymentioning
confidence: 99%
“…In contrast, Lynch and Cohn (2017) take as their starting point a topic frequently reduced to the broader politics of life -blood donation. They argue that the exclusion of the routine, material aspects of blood donation in much research masks a hidden multiplicity of concepts.…”
Section: The Collectionmentioning
confidence: 99%